ACM International Conference on Interactive Tabletops and Surfaces 2010
DOI: 10.1145/1936652.1936662
|View full text |Cite
|
Sign up to set email alerts
|

Towards a formalization of multi-touch gestures

Abstract: Multi-touch is a technology which offers new styles of interaction compared to traditional input devices like keyboard and mouse. Users can quickly manipulate objects or execute commands by means of their fingers and hands. Current multi-touch frameworks offer a set of standard gestures that are easy to use when developing an application. In contrast, defining new gestures requires a lot of work involving low-level recognition of touch data. To address this problem, we contribute a discussion of strategies tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 21 publications
2
70
0
Order By: Relevance
“…One type of technology that supports touch input is the multitouch surface. The multi-touch is a collaborative technology that allows co-located individuals to collaborate, while interacting together on one surface simultaneously using their fingers as a means of touch input instead of a keyboard or mouse (Morris et al, 2006;Hornecker et al, 2008;Kammer, Wojdziak, Keck, Groh & Taranko, 2010;Hunter & Maes, 2008). Using this type of input is a direct way of interacting with the screen and it has been reported to feel like a more natural approach.…”
Section: Collaboration and Synchronous Gesturesmentioning
confidence: 99%
See 2 more Smart Citations
“…One type of technology that supports touch input is the multitouch surface. The multi-touch is a collaborative technology that allows co-located individuals to collaborate, while interacting together on one surface simultaneously using their fingers as a means of touch input instead of a keyboard or mouse (Morris et al, 2006;Hornecker et al, 2008;Kammer, Wojdziak, Keck, Groh & Taranko, 2010;Hunter & Maes, 2008). Using this type of input is a direct way of interacting with the screen and it has been reported to feel like a more natural approach.…”
Section: Collaboration and Synchronous Gesturesmentioning
confidence: 99%
“…Using a multi-touch surface in a collaborative environment poses many benefits, such as being able to see other participants' body language, participants' pointing to objects on the surface and discussing the work at hand together (Clifton et al, 2011). Collaborative drawing and modelling can also be successfully achieved on a multi-touch surface (Morris et al, 2006;Hornecker et al, 2008;Kammer et al, 2010;Hunter & Maes, 2008;Sams, Wesson & Vogts, 2011).…”
Section: Collaboration and Synchronous Gesturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on multitouch interfaces [18,54] have demonstrated the superiority of gestural interaction over mouse-driven WIMP paradigms. Kammer et al [33] formalize gestures according to the semantics, pragmatics and syntactics of interaction, while Yee [59] discusses concerns regarding direct and indirect gestural interactions. Visual analytics systems such as Tableau [51] and TaP [21] map interactions and gestures from the UI layer to a set of database query templates, without considering the contents of the database itself.…”
Section: Related Workmentioning
confidence: 99%
“…Kammer et al [85] describe GeForMT (Gesture Formalization for MultiTouch) which is defined using semiotic with three components and their scope: syntactic (symbols), semantics (meaning) and pragmatics (interpretation). This language permits the representation of multi-touch gestures.…”
Section: Gesture Representationmentioning
confidence: 99%